(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Understanding the factors that contribute to a positive tourist experience is critical in maintaining and improving tourism competitiveness. This study determined the influence of destination perception and satisfaction on destination loyalty among tourists in a private villa on Turks and Caicos Island. The study utilized a descriptive-correlational research design. Data were collected from a sample of 100 tourists using the survey questionnaires of Umit Basaran (2016) for destination image, Ruiz E., et. al. (2017) for tourist satisfaction; and Kanwel et al. (2019) for destination loyalty. Descriptive statistics and multiple regression analysis were employed. The findings reveal that participants had a highly favorable perception on the cognitive component and a very highly favorable perception on the affective component of the destination. They were highly satisfied with various aspects of the villa such as destination facilities, safety, cleanliness, guest service, and entertainment; and exhibited a very high level of destination loyalty. The study also found that tourists’ perception of destination image and tourist satisfaction significantly influenced destination loyalty, with safety having the highest positive influence. However, further findings of the study also highlight a negative influence between guest service satisfaction and destination loyalty, indicating that as tourists become highly satisfied with guest service, their loyalty tends to decrease. Thus, the study emphasizes the crucial role of managing and enhancing effectively a destination’s image, as well as providing top-notch tourist experiences, in promoting tourist loyalty. By prioritizing these factors, destination managers can foster a positive and lasting impression of the destination that encourages tourists to return and recommend the destination to others.